Fatty acid intake and rumen fatty acid composition is affected by pre-grazing herbage mass and daily herbage allowance in Holstein dairy cows - Palladino, Rafael A.; O´Donovan, Michael; Kenny, David A. (Spanish Journal of Agricultural Research, 2014)
The objective of this study was to investigate the effect of level of pre-grazing herbage mass (HM) and daily herbage allowance (DHA) on the fatty acid (FA) intake and composition of ruminal content of grazing dairy cows. Four rumen fistulated Holstein-Friesian dairy cows were allocated to either a high or low HM (1700 vs 2600 kg DM ha-1) and within herbage mass treatment further allocated to a high or low DHA (20 vs 16 kg of DM cow-1 day-1) in a 4 × 4 Latin square design. Total FA intake and linolenic acid (LNA) intake was higher for cows on high DHA (p<0.05). Ruminal oleic acid, linoleic and LNA were not affected by treatments. Ruminal stearic acid (C18:0) and vaccenic acid (VA) concentrations were higher at low HM (43.6 and 14.8 g/100 gof FA respectively; p<0.01) compared to high HM (42.0 and 12.5 g/100 gof FA respectively for C18:0 and VA). Cows grazing high DHA had higher ruminal concentration of VA (15.3 g/100 gof FA; p<0.01) than low DHA (12.1 g/100 gof FA). Regarding milk FA composition, only some of the milk FA varied across treatments, being the VA and LNA concentrations higher at low HM (p<0.05). These data suggest that low HM and high DHA, at least within the range studied here, promotes the accumulation of ruminal VA which could be available for subsequent conversion within the mammary gland to the human health promoting c9,t11 isomer of conjugated linoleic acid.